A study on the use of repetition in English print advertisements in newspapers and magazines = Nghiên cứu về việc sử dụng phép lặp trong quảng cáo Tiếng anh trên báo và tạp chí - Bùi, Hạnh Mai (2021)
The principal objective of this research is to figure out the typical types of repetition and their frequency in English print advertisements in newspapers and magazines. The research method involved observation of document .Thirty-five English print advertisements were collected based on a set of four criteria. The data analysis procedure led the researcher to three main kinds of repetition which were repetition of sounds, words and structures; and eight subtypes including rhyme, chime, assonance and alliteration, anaphora, epistrophe, epanalepsis, anadiplosis and parison. Among these types, word repetition was reported to be applied the most in the sampled ads, however, when coming to a more detailed classification, anaphora became the most popular repetition pattern. Although the research was conducted seriously and carefully, limitations were inevitable. Because of the limitation in data sources, the researcher could not carry out the study in a larger scale. Due to the small number of samples, generalization was far from being achieved. Besides, the study only focused on the English print advertisements in newspapers and magazines, therefore, the researcher would like to call for further research in this issue with more types of advertising being investigated.